Nigerian Counsellors' Awareness and Readiness to Use Social Media Technology for Counselling and National Development - Popoola, Balqis Olabisi; Kareem, Yusuf Babatunde; Oduola, Olayemi Zainab (Coution: Journal Counseling and Education, 2025)
This study aimed to investigate the awareness and readiness of Nigerian counsellors to propagate counselling services via social media platforms to attain national goals in the era of technology. The study used a descriptive research design and a mixed-method approach to collect and analyse data from Nigerian Counsellors in tertiary institutions. The study found that while Nigerian counsellors are generally familiar with social media platforms and tools, there are barriers to usage, such as poor internet connectivity, lack of training and support, and cultural and religious concerns. The study's findings highlight the potential benefits of social media use in promoting counselling services in Nigeria, including increased collaboration among counsellors and the ability to reach a wider audience, especially in remote areas. The study recommends providing training and support to educators with limited digital literacy skills and the need to address cultural and religious concerns that may impede the adoption of social media for counselling services and purposes. Overall, this study's findings suggest that social media has the potential to play a significant role in promoting counselling services in Nigeria. However, there is a need to address barriers to usage and provide appropriate training and support to counsellors.